"Programmirovanie" ili "postroenie"? - Smirnov, M. R. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper was to hold on the discussion about TST developing. The author outspeaks his opinion for several disputable questions, which have been earlier pointed by other participants of the discussion. He focused at the statement and content of notions "programming" and "constructing". The author emphasized the necessity of mathematically modeled and scientifically substantiated planning of training loads.